(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze spelling errors in poetry texts written by class X students of SMK Negeri 1 Tugala Oyo in the 2024/2025 academic year. This research uses a qualitative descriptive method that focuses on describing in depth the forms of spelling errors made by students. Data were collected through documentation of 30 poetry texts written by students and semi-structured interviews with Indonesian language teachers to obtain supporting information about spelling learning in class. The data were analyzed through the stages of error identification, classification based on the type of error, and interpretation of the cause by referring to the General Guidelines for Indonesian Spelling (PUEBI). The results show that the spelling errors found include the use of capital and non-capital letters, the use of punctuation marks, word writing, and the writing of abbreviations and acronyms. This finding indicates that students’ understanding of spelling rules is still low, so teachers need to strengthen spelling learning through additional literature materials and practice in applying spelling in writing literary works.